Perspective and Challenge of Tidal Power in Bangladesh - Md. Alamgir Hossain; Md. Zakir Hossain; Md. Mijanur Rahman; Md. Atiqur Rahman (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Tidal power can play a vital role in integrating as new source of renewable energy to the off-grid power connection in isolated areas, namely Sandwip, in Bangladesh. It can reduce the present energy crisis and improve the social, environmental and economical perspective of Bangladesh. Tidal energy is becoming popular around the world due to its own facilities. The development of any country largely depends on energy sector improvement. Lack of energy sector is because hampering of progress of any country development and energy sector will be stable by only depend on sustainable energy sources. Renewable energy is the only sustainable solution of secure energy which is environmental friendly. Bangladesh has a huge potential of tidal power at different locations but effective measure on this issue have not been considered sincerely. This paper summarizes the current energy scenario and Bangladesh can produce power approximately 53.19MW across the country to reduce the growing energy demand utilizing tidal energy as well as it is shown that Sandwip has high potential of producing tidal power which is approximately 16.49MW by investing only US $10.37 millions. Besides this, cost management for tidal power plant also has been discussed.